(untitled) (Discourse of Law and Administration, 2019)
This article is devoted to selected problems in the field of general preventive impact of punitive measures. The paper paid special attention to the current status of general prevention, one of the directives of sentencing in criminal cases, and to the consequent implications for criminal policy. In addition, the article separately deals with the issue of the correct application of the selected criminal punishment solutions in the process of shaping legal awareness of the society. Based on the considerations, it was found that for general prevention, its status as a sui generis penal conception, defining certain punishment standards, is more convincing.